Effectiveness of Mastitis management instructional video on knowledge of tribal farmers in northern hills zone of Chhattisgarh - MOOVENTHAN, P; KADIAN, K S; KUMAR, R SENTHIL; KUMARESAN, A; MANIMARAN, A; SELVAN, A SAKTHIVEL (The Indian Journal of Animal Sciences, 2017)
Mastitis is the inflammation of udder parenchyma and mostly occurs due to an invasion of bacteria through its teat canal from environment or during milking procedure. Mastitis is a multifactorial threshold trait resulting from interaction between genetic components of the host, infectious agents and environmental factors (Keviletsu and Yadav 2009).This disease can be identified by abnormalities in the milk, udder parenchyma with or without systemic illness. Mastitis is the most common and costly disease of dairy cattle today and remains one of the major problems for the dairy industry. Significant economic losses are mostly due to pathogen-mediated damage of milk secreting tissue of udder, lower milk yield and its degraded quality, early culling, loss of genetic potential, higher veterinary expenses, and increased labour cost for a farmer. Among the several barriers in achieving the milk production targets, mastitis continues to remain as a most challenging impediment, since the affected quarters show 30% less productivity and cow loses about 50% of production (NAAS 2013). In the affected animals, the milk yield is reduced considerably. Estimates of milk yield loss by different workers range from 100 to 500 kg/cow per lactation. When clinical mastitis occurs, additional costs result from discard of abnormal milk, cost of drugs and veterinary services. According to a study, the estimated loss following clinical mastitis in cows was almost 700 kg in first lactation and 1, 200 kg in the second or higher lactation.